(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the changes in the serum insulin levels in alloxan induced diabetic albino rats in comparison with oral hypoglycemic drugs. Study Design: An experimental study. Place and Duration of Study: This study was conducted at Al Tibri Medical College Karachi during December 2012 to December 2013. Materials and Methods: The present study was conducted on 60 Albino rats which were group from A to F consisting of 10 rats in each group. These groups were further divided into two sub groups which were treated with low dose and high dose of the cinnamon and oral hypoglycemic drugs. Results: The results showed that there is significant reduction in serum insulin level in the alloxan treated group animals which was improved in group C animals treated with low dose of cinnamon extract in alloxan induced diabetic rats. Also animals in group D and group E treated with tolbutamide and acarbose respectively showed higher increase in serum insulin level as compared with cinnamon extract treated groups, however when cinnamon extract was used in combination with tolbutamide or acarbose it showed synergetic effects. Conclusion: Tolbutamide and Acarbose treated groups showed better anti diabetic effect by increasing the serum insulin level in comparison with cinnamon extract treated groups when used individually. This effect was enhanced when cinnamon extract was used in combination with either tolbutamide or acarbose.